Utilizar la prospectiva estratégica para pensar y actuar ante un futuro incierto del mundo del trabajo - Rafael Peels; Aída Ponce Del Castillo (Organización Internacional del Trabajo (OIT), 2024)
The world of work is experiencing multiple transformations driven by automation and digitalization, environmental changes, (de)globalization, and demographic shifts, among other factors. The effects of the COVID-19 pandemic, worsening geopolitical tensions, environmental disasters and armed conflicts have further exacerbated these realities to the extent that today we are living in a poly- or perma-crisis. These multiple pressures and crises impact the world of work and oblige trade unions to reflect and act upon uncertainty and change. Increasingly, trade unions worldwide do this, while exploring different tools and methods to think and act upon their future readiness. One method that can be particularly useful is strategic foresight. The paper is the first of its kind, documenting trade union experience worldwide on doing foresight. The research was done through literature review, desk research and direct participation in foresight workshops. Foresight training courses and workshops were organized in various regions in the world (i.e. Europe, the Arab States, Africa, Asia and the Pacific) in the period 2019-2023. The objective of this paper is to provide concrete examples and lessons learned for trade unions that are willing to experiment with strategic thinking and foresight. The paper builds further on the foresight literature by paying particular attention to the context of trade unionism, and trade union realities in different regions.
Keywords: 330; Gewerkschaft; Zukunftsforschung; Welt